2008
DOI: 10.1111/j.1471-0528.2008.01870.x
|View full text |Cite
|
Sign up to set email alerts
|

Customised birthweight percentiles: does adjusting for maternal characteristics matter?

Abstract: Objective The objective of this study was to determine whether the improved prediction of risk for perinatal mortality obtained with the use of a customised birthweight standard can also be obtained with the use of a non-customised but intrauterine-based standard.Design Population-based cohort study.Setting Sweden.Population Births in the Swedish Medical Birth Register between 1992 and 2001 (n = 782 303) with complete data on birthweight, gestational age, sex, maternal age, pre-pregnancy body mass index, heigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
110
3
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(119 citation statements)
references
References 27 publications
3
110
3
3
Order By: Relevance
“…[32][33][34][35][36][37] However, our results (Figure 3) indicate that there are large differences in infant mortality rates among races/ethnicities, even within the same fetal size category, which supports the necessity to adjust for race/ethnicity. Unfortunately, the current data do not allow us to look at some other components of customisation, such as maternal height and weight.…”
Section: Weaknesses and Interpretationcontrasting
confidence: 38%
“…[32][33][34][35][36][37] However, our results (Figure 3) indicate that there are large differences in infant mortality rates among races/ethnicities, even within the same fetal size category, which supports the necessity to adjust for race/ethnicity. Unfortunately, the current data do not allow us to look at some other components of customisation, such as maternal height and weight.…”
Section: Weaknesses and Interpretationcontrasting
confidence: 38%
“…[15][16][17] Although the customized standards included ethnicity or birthplace, among other individual characteristics, the independent contribution of maternal geographic origin was not reported in those studies. Mikolajczyk and colleagues 18 showed that individually customized standards did not improve the discrimination of adverse perinatal outcomes beyond using a fetal growth standard solely based on maternal country of birth, which suggests that maternal birthplace is a sufficient characteristic for customization of birth-weight curves.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] To date, there is no consensus regarding the minimal set of maternal characteristics that improves detection of adverse outcomes through the use of customized charts. [13][14][15][16][17] So far, the single characteristic that has been shown to influence the size of newborns in this way is maternal country of birth. 18 We conducted a study to determine whether use of world region-specific birth-weight curves would be more accurate than use of a single birth-weight curve based on infants of Canadian-born women in predicting adverse neonatal and obstetric outcomes known to be associated with small for gestational age and large for gestational age among infants born to immigrant women in Canada.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have demonstrated that those fetuses identified as SGA only by customized centiles are at increased risk of adverse outcome, while those considered as SGA only by population centiles have similar outcomes to the appropriately grown fetsues [12]. However, the concept of customization is controversial at present, partially due to the fact that some of the factors which influence fetal size, might not have a physiological effect, and that they themselves are known pathological risk factors for stillbirth -such as advanced maternal age, increased maternal weight and ethnic origin [13][14][15].…”
Section: Highlightsmentioning
confidence: 99%